Hubungan Status Akreditasi Puskesmas dengan Tingkat Kepuasan Pasien Rawat Jalan di Puskesmas Borong Kabupaten Manggarai Timur - Bernadina Alfionita; Rina Waty Sirait; Tasalina Y P Gustam (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Accreditation of community health centers (Puskesmas) is a systematic effort to improve the quality of health services through the fulfillment of established standards. Borong Community Health Center, which has achieved Main (Utama) Accreditation, is expected to provide high-quality services that positively influence patient satisfaction. This study aims to determine the relationship between accreditation status and patient satisfaction, assessed through five dimensions of service quality (SERVQUAL), namely tangibles, reliability, responsiveness, assurance, and empathy. This research used a quantitative method with a cross-sectional design. The sample consisted of 90 respondent, selected using accidental sampling. Data were collected through a structured questionnaire and analyzed using the Chi-Square test with SPSS software. The results showed a significant relationship between accreditation status and patient satisfaction in the dimensions of reliability (p = 0.002), responsiveness (p = 0.004), and assurance (p = 0.001). Meanwhile, the dimensions of tangibles (p = 0.802) and empathy (p = 0.202) did not show a significant relationship with patient satisfaction. These findings indicate that Main Accreditation primarily enhances service quality related to service consistency, responsiveness, and assurance, whereas physical facilities and empathetic interactions have not become dominant determinants of satisfactio. In conclusion, Main Accreditation contributes to improved patient satisfaction mainly through strengthening service processes, rather than through improvements in physical aspects or interpersonal interactions. It is recommended that the health center continue to enhance the tangibles and empathy dimensions to further improve overall service quality.